SITUATIONAL ANALYSIS OF EDUCATIONAL WASTAGE RATES IN PUBLIC UNIVERSITIES PROGRAMMES IN ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2024)
The study investigated the situations of educational wastage rates in public universities programmes in Anambra State. Eight research questions guided the study and four null hypotheses were tested at 0.05 level of significance. Descriptive survey research design was adopted for the study. The population of the study consisted of 18,636 respondents (14,674 undergraduates, 3,767 postgraduates and 195 administrators) in public universities in Anambra State. The sample size for the study was 9,978 respondents (8,809 undergraduates, 1,087 postgraduates and 82 administrators) drawn using two-stagesampling procedure involving purposive and simple random sampling techniques. Researcherdeveloped instrument titled ‘Inventory Proforma for Educational Wastage (IPEW)’ was used for data collection. The instruments were face validated by three experts who were lecturers from the Faculty of Education, Nnamdi Azikiwe University, Awka. The instrument was not subjected to test of internal consistency due to the fact that it was just employed for gathering existing data. The researcher together with four research assistants collected data for the study using the direct approach method and 100% return was recorded. Percentage was used to answer research questions, whereas chisquare was used to test hypotheses. The finding of the study revealed among others that students recorded low rate of dropout and high completion rate of undergraduate programme in public universities in Anambra State. It was also found that students recorded moderate rates of dropout and completion of postgraduate programme in public universities in Anambra State. Based on the findings, it was recommended among others that university management should inaugurate a committee to sensitize both undergraduates and postgraduate students on the need to avoid dropping out from their programme
Keywords: Educational Wastage Rates, University, Dropout, Completion